Preparation of new bioactive hybrid bone cements containing Bis-GMA derivatives as a prepolymer - Park, Bang-Ju; Park, Kwideok; Ahn, Kwang-Duk; Chin, Yong-Ok; Han, Dong Keun (WILEY-V C H VERLAG GMBH, 2006)
Novel organic-inorganic hybrid bioactive bone cements containing bisphenol-A-glycidyl methacrylate (Bis-GMA) derivatives and a bioactive inorganic filler were prepared for othorpedic applications. The Bis-GMA derivatives, such as 3MA and a 3MA mixture (3MA mix), were synthesized by blocking one or two of the hydroxyl groups of the Bis-GMA so as to use it as a prepolymer. Four organic prepolymers, such as Bis-GMA, 3MA, 3MA 50 and 3MA mix, and an inorganic filler, AW-GC, were used for the preparation of the bioactive bone cements and their characteristics were evaluated. As compared with the Bis-GMA control, the new bioactive bone cements containing the Bis-GMA derivatives exhibited appropriate curing times, low polymerization shrinkage, low water absorption and solubility as well as high mechanical properties. In particular, the bioactive bone cement containing 3MA mix and AW-GC had higher bending and compressive strengths than the Bis-GMA one.
Keywords: BIOLOGICAL PROPERTIES; MECHANICAL-PROPERTIES; HIGH-VISCOSITY; HYDROXYAPATITE; FILLER; WOLLASTONITE; SHRINKAGE; STRENGTH; APATITE